248 The experience in pelvic exenteration in patients with advanced and recurrent cervical cancer in Belarus. (13th November 2020) - Matylevich, O; Sukonko, O; Mirilenko, L
Abstract : Objective: To determine the efficacy of pelvic exenteration (PE) in patients with locally advanced, persistent and recurrent cervical cancer (CC). Methods: A retrospective study was performed of 30 patients with locally advanced, persistent and recurrent CC who underwent PE in 2006–2012. Anterior PE was performed in 24 (80%) patients, posterior PE in 2 (7%) and total PE in 4 (13%). Results: The mean operation time was 279.5 min. Urine derivation in 28 patients was performed in the following ways: 7 (25%) patients were subjected to ureterostomy, 21 (75%) had plastic interventions for neocyst formation. Fecal diversion performed in 5 patients by end colostomy (Hartman's procedure) and in one patient rectum resection was performed. Radical surgery was performed in 70% (21 of 30) of the patients. The median follow-up time of the 28 patients was 76.3 months. During the follow-up period, 19 (68%) patients died of the underlying disease with no deaths of other causes. The median survival was 15.5 months, 5-year survival – 32% (SE 8.8%). The median survival after radical surgery was 37.9 months vs 5.5 months after nonradical one. Five-year cause-specific survival after radical surgery was 74% (SE 10.1%; 95% CI 49–91%), after nonradical one – 33% (SE 15.7%). Conclusion: Surgical radicality has been established to be a clinically and statistically significant factor of death risk: the radical surgery enables to reduce the death risk 3.5-fold (95% CI 1.4–9.0; p=0.009), to increase the median survival 6.9-fold, 5-year survival from 11% (SE 10.5%) to 42% (SE 11.3%, 95% CI 20–67%).